Enhanced Electrocatalytic Activity of Pt Particles Supported on Reduced Graphene Oxide/Poly(3,4-ethylenedioxythiophene) RGO/PEDOT Composite towards Ethanol Oxidation - Juanito Raphael F. Foronda; Stellar Marie R. Cabrera; Darrel L. Cumpas; Paolo Gio A. Villar; Joshua L. Tan; Bernard John V. Tongol (Journal of Chemistry)
Catalysts in fuel cells are normally platinum based because platinum exhibits high electrocatalytic activity towards ethanol oxidation in acidic medium. However, bulk Pt is expensive and rare in nature. To reduce the consumption of Pt, a support material or matrix is needed to disperse Pt on its surface as micro- or nanoparticles with potential application as anode material in direct ethanol fuel cells (DEFCs). In this study, a composite material consisting of platinum particles dispersed on reduced graphene oxide/poly(3,4-ethylenedioxythiophene) (RGO/PEDOT) support was electrochemically prepared for ethanol oxidation in sulfuric acid electrolyte. PEDOT, a conductive polymer, was potentiodynamically polymerized from the corresponding monomer, 0.10 M EDOT in 0.10 M HClO4 electrolyte. The PEDOT-modified electrode was used as a substrate for exfoliated graphene oxide (EGO) which was prepared by electrochemical exfoliation of graphite from carbon rod of spent batteries and subsequently reduced to form RGO. The Pt/RGO/PEDOT composite gave the highest electrocatalytic activity with an anodic current density of 2688.7 mA·cm−2 at E = 0.70 V (versus Ag/AgCl) towards ethanol oxidation compared to bare Pt electrode and other composites. Scanning electron microscopy (SEM) revealed the surface morphology of the hybrid composites while energy dispersive X-ray (EDX) confirmed the presence of all the elements for the Pt/RGO/PEDOT composite.